Rodzina von Seydel z Luboszyc. Przyczynek do badań prozopograficznych szlachty dolnołużyckiej = Family von Seydel from Luboszyce. Contribution to prozopographic studies Lower Lusatian nobles - Konopnicka, Małgorzata; Ostrowski, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1764 Christian Gottfried (von) Seydel acquired village Luboszyce. It was located several kilometers away from Gubin at Lower Lusatia which was part of Saxony until 1815. Then this region came under Prusian rule. Von Saydel family appeared in Luboszyce at the end of XVIII century and that was recorded in several sources. It was possible to reconstruct family further story by studying gravestones, originally scattered on cemeteries in Polanowice and Luboszyce.
Keywords: Dolne Łużyce; Luboszyce; szlachta; epigrafika; prozopografia; Lower Lusatia; gentry; epigraphic; prosopography